ICT IN EDUCATION: ITS BENEFITS, DIFFICULTIES, AND ORGANIZATIONAL DEVELOPMENT ISSUES - Adi Suryani (Institut Teknologi Sepuluh Nopember, 2008)
This essay describes some benefits of implementing ICT in classroom, especially within the area of collaborative and self-managed learning. However, implementing ICT in classroom is not an easy and simple matter. There are many issues which should be addressed. Those issues range from the school culture, teachers barriers, finance, leadership, curriculum, and ethical issues. Those problems are experienced by both developed and developing countries. This also refutes a widespread assumption that developing countries experience more barriers for implementing ICT than developed countries.